2014
DOI: 10.1523/jneurosci.1776-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Theta-Burst Stimulation of the Lateral Cerebellum Increases Functional Connectivity of the Default Network

Abstract: Cerebral cortical intrinsic connectivity networks share topographically arranged functional connectivity with the cerebellum. However, the contribution of cerebellar nodes to distributed network organization and function remains poorly understood. In humans, we applied theta-burst transcranial magnetic stimulation, guided by subject-specific connectivity, to regions of the cerebellum to evaluate the functional relevance of connections between cerebellar and cerebral cortical nodes in different networks. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
136
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(154 citation statements)
references
References 51 publications
7
136
2
1
Order By: Relevance
“…The cerebellar Crus I is also connected functionally with DMN in the resting state (Buckner et al, 2011). Moreover, the theta-burst stimulation of this region increases the functional connectivity of DMN, suggesting that the cerebellum plays an active role in modulating the function of DMN (Halko et al, 2014). Therefore, the present results suggest that internal processing, including memory retrieval, occurs during spontaneous eyeblinks by concurrently activating the brain regions connected functionally to DMN.…”
Section: Blink-related Switching Between Internal and External Orientsupporting
confidence: 52%
See 1 more Smart Citation
“…The cerebellar Crus I is also connected functionally with DMN in the resting state (Buckner et al, 2011). Moreover, the theta-burst stimulation of this region increases the functional connectivity of DMN, suggesting that the cerebellum plays an active role in modulating the function of DMN (Halko et al, 2014). Therefore, the present results suggest that internal processing, including memory retrieval, occurs during spontaneous eyeblinks by concurrently activating the brain regions connected functionally to DMN.…”
Section: Blink-related Switching Between Internal and External Orientsupporting
confidence: 52%
“…For example, many neuroimaging studies reported that the hippocampus often shows concurrent activation with the DMN, particularly during tasks that require self-referenced memory retrieval (Greicius et al, 2004;Vincent et al, 2006). In addition to the hippocampus, the recent fMRI studies revealed that the cerebellum cortex has a strong functional connectivity with the DMN (Buckner et al, 2011;Halko et al, 2014). Thus, I speculate that these brain regions which have dense functional connectivity with the DMN also showed blink-related activation.…”
Section: Introductionmentioning
confidence: 95%
“…As in the study by Eldaief et al [60], Halko et al [62] used the baseline rs-fMRI of participants to localize the cerebellar node of the DMN. Stimulation through iTBS of the DMN-cerebellum node resulted in increased FC of cortical nodes of the DMN.…”
Section: Local and Distal Connectivity Effects Of Nibsmentioning
confidence: 99%
“…Stimulation through iTBS of the DMN-cerebellum node resulted in increased FC of cortical nodes of the DMN. Targeting the midline cerebellum, which is not part of the DMN, increased FC of the dorsal attention network [62]. Rastogi et al [63] found reduced FC in frontal and parietal cognitive regions after cTBS of the crus I of the lateral cerebellum.…”
Section: Local and Distal Connectivity Effects Of Nibsmentioning
confidence: 99%
“…Recently, based on rs-fMRI, the cerebellum has been divided into subregions that are coupled with specific cortical networks (Buckner et al, 2011; Habas et al, 2009; O'Reilly et al, 2010). In a large sample of healthy subjects (n=1000), lateral cerebellar areas including crus I/II were shown to be functionally connected with the DMN (Buckner et al, 2011), and neurostimulation of this region was shown to modulate functional connectivity specifically with and between cortical DMN areas (Halko et al, 2014). It remains unknown whether intrinsic cerebellar DMN (CerDMN) FC with cortical networks is altered in ADHD.…”
Section: Introductionmentioning
confidence: 99%